2018
DOI: 10.1186/s12885-018-5110-2
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of afatinib dose on outcomes of advanced EGFR-mutant NSCLC patients with brain metastases

Abstract: BackgroundAfatinib is an oral irreversible epidermal growth factor receptor (EGFR) tyrosine-kinase inhibitor (TKI) indicated in first-line treatment of advanced EGFR-mutant (EGFRm+) non-small cell lung cancer (NSCLC). Dose dependent side effects can limit drug exposure, which may impact on extracranial and central nervous system (CNS) disease control.MethodsWe performed a retrospective study of 125 patients diagnosed with advanced EGFRm+ NSCLC treated with first-line afatinib at a tertiary Asian cancer center,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
3
18
2
1
Order By: Relevance
“…Similar beneficial response was not seen in such patients treated with first-generation EGFR -TKIs [27]. Contrary to the findings by Tan et al [22], the present study did not find a significantly shorter mPFS among patients with symptomatic brain metastases receiving first-line afatinib [22]. This favorable outcome could be explained by the uniform afatinib starting dose of 40 mg once daily and the comprehensive brain surgery or radiotherapy approach in the present study cohort.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Similar beneficial response was not seen in such patients treated with first-generation EGFR -TKIs [27]. Contrary to the findings by Tan et al [22], the present study did not find a significantly shorter mPFS among patients with symptomatic brain metastases receiving first-line afatinib [22]. This favorable outcome could be explained by the uniform afatinib starting dose of 40 mg once daily and the comprehensive brain surgery or radiotherapy approach in the present study cohort.…”
Section: Discussioncontrasting
confidence: 94%
“…The former study included 14 patients who achieved a partial response or at least 6 months of stable disease when on first-line afatinib while the latter study only involved patients with ECOG 0–2 which could have contributed to the longer mPFS. Similar to the present study, Liang et al [21], Tan et al [22] Kim et al [26] and Tanaka et al [24] also consistently highlighted a longer mPFS and better ORR in patients with tumors harboring exon 19 deletion treated with first-line afatinib compared to those with exon 21 L858R point mutation. In patients with complex or rare EGFR mutations treated with first-line afatinib, the present study and another three real-world studies reported a modest mPFS and ORR [21, 22, 27].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, Tan et al revealed that among patients with advanced EGFR mutant NSCLC with brain metastasis, the initiation of 40 mg afatinib once daily was associated with improved PFS compared to 30 mg once daily. 23 We did not observe this outcome, which may result from our relatively small sample of patients with baseline brain metastasis treated with 30 mg afatinib.…”
Section: Discussionmentioning
confidence: 74%
“…In a retrospective study of 125 patients who received treatment with afatinib at an Asian cancer treatment center, the median PFS was longer in patients with brain metastases who started treatment with afatinib 40 mg/day (n=17) than in 25 patients who initiated 30 mg/day. 28 Pharmacokinetic analysis of patients in LL3 found that afatinib trough plasma concentrations were higher on day 22 in patients who subsequently had a reduction in dose from 40 mg/day to 30 mg/day due to TRAEs than in those who remained on 40 mg/day. Subsequently, on day 43, afatinib trough plasma concentrations in the patients now on 30 mg/day were similar to those in patients who had remained on 40 mg/day.…”
Section: Dovepressmentioning
confidence: 99%